1998
DOI: 10.1046/j.1432-1327.1998.2540238.x
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct structures of α‐conotoxin GI in aqueous solution

Abstract: The detailed analysis of conformational space of A-conotoxin GI in aqueous solution has been performed on the basis of two-dimensional NMR spectroscopy data using multiconformational approach. As the result, two topologically distinct interconvertible sets of GI conformations (populations of 78% and 22%) have been found. A common feature of the two sets is the Asn4-Cys7 β-turn. The Gly8 to Tyr11 region has a structure of right-handed helical turn in the major set and two sequential bends in the minor one. N-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 4 publications
4
52
0
Order By: Relevance
“…Because of trans-cis isomerization of prolines, minor peaks originating from a cis-conformer were noted. Similar cis conformers have been observed in other ␣-/␣A-conotoxins as well (13,27,34,41). Detailed analyses of NMR data and structure calculation have been carried out for the trans-isomer.…”
Section: Nmr Spectroscopy-completesupporting
confidence: 63%
“…Because of trans-cis isomerization of prolines, minor peaks originating from a cis-conformer were noted. Similar cis conformers have been observed in other ␣-/␣A-conotoxins as well (13,27,34,41). Detailed analyses of NMR data and structure calculation have been carried out for the trans-isomer.…”
Section: Nmr Spectroscopy-completesupporting
confidence: 63%
“…3 is that of the major conformation, but the structure of the minor conformation has not been reported. However, for CTx GI, which has a similar pharmacological fingerprint to CTx MI, atomic coordinates of both major and minor conformations have been reported (31). Comparison of all reported structures of CTx GI indicates that the major conformers of CTx MI and GI are structurally similar (31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 99%
“…However, for CTx GI, which has a similar pharmacological fingerprint to CTx MI, atomic coordinates of both major and minor conformations have been reported (31). Comparison of all reported structures of CTx GI indicates that the major conformers of CTx MI and GI are structurally similar (31)(32)(33)(34). If the two conformers for CTx GI are comparable to those for CTx MI, we can ask whether any of the four bioactive residues change positions between major and minor conformations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous results suggested that some a3/5-conotoxins also exhibit asymmetric elution peaks on HPLC following oxidation, and have two conformations in aqueous condition [13,[21][22][23], which differ in the second Cys loop and peptide termini region [23]. It would be difficult to determine which conformer is more favorable for peptide activity on nAChRs.…”
Section: Discussionmentioning
confidence: 99%